Current needs for human and medical genomics research infrastructure in low and middle income countries (2016)
Genomics has facilitated the identification of a large number of genetic variants that are causal and/or risk factors for both rare and common human diseases. Low and middle income countries (LMIC) represent a large proportion of the human population, with distinct health priorities from the developed world. There have been some initiatives in LMIC focused on medical genomics research. We review successful examples of existing genomics centres in LMIC and suggest some recommendations to develop the research infrastructure that is needed in LMIC. There is an urgent need to improve local infrastructures of many LMIC to carry out medical genomics research.